2003
DOI: 10.21273/hortsci.38.2.288
|View full text |Cite
|
Sign up to set email alerts
|

Cold Tolerance in 'Kousui' Japanese Pear and Possibility for Avoiding Frost Injury by Treatment with n-Propyl Dihydrojasmonate

Abstract: Effects of n-propyl dihydrojasmonate (PDJ) treatment on flowers of Japanese pear 'Kousui' (Pyrus pyrifolia Nakai cv. Kousui) during spring frost were investigated to study mechanisms for avoiding spring frost injury. PDJ applied during the flowering period resulted in a lower injury index for the ovules and pistils after freezing tests. Average ion leakage in control flowers was 37.9% during the balloon stage at -5 °C, while the flowers treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…In our study, the fact that ABA increased in PDJ-or spermine-treated fruit suggests that these treatments may be effective for improving chilling tolerance. It has been shown that the application of PDJ spray in the blooming period decreased spring frost injury in Japanese pears (Pynus pyrifolia Nakai) based on the increase of the sugar concentration in the fruit (Secozawa et al 2003). In our study, although the branches with fruit were placed in darkness, the possibility of sugar accumulation or sugar translocation from leaves in the PDJ-applied fruit that exhibited decreased lowtemperature injury should also be investigated.…”
Section: Discussionmentioning
confidence: 92%
“…In our study, the fact that ABA increased in PDJ-or spermine-treated fruit suggests that these treatments may be effective for improving chilling tolerance. It has been shown that the application of PDJ spray in the blooming period decreased spring frost injury in Japanese pears (Pynus pyrifolia Nakai) based on the increase of the sugar concentration in the fruit (Secozawa et al 2003). In our study, although the branches with fruit were placed in darkness, the possibility of sugar accumulation or sugar translocation from leaves in the PDJ-applied fruit that exhibited decreased lowtemperature injury should also be investigated.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism of JA against CI is unclear. It has been observed that PDJ application in the blooming period decreased spring frost injury in Japanese pears (Pyrus pyrifolia Nakai) (Sekozawa et al, 2003). It was concluded that the increase of sugar content in the PDJ-treated fl ower was related to the alleviation of frost injury.…”
Section: Resultsmentioning
confidence: 99%
“…Browning of the female tissue due to low-temperature exposure has been observed (Oya, 2012;Sakuma et al, 2013;Sato, 1982). Sugar accumulation inhibits intracellular freezing and prevents frost injury in the Japanese pear flower (Sekozawa et al, 2003). The sugar content of a Japanese pear bud decreases from winter to spring (Sekozawa, 2004) whereas in the pollen, starch is turned into sugar, and sugar accumulates in the pollen grain as it matures (Hayashi and Tanabe, 1991).…”
Section: Sensitive Pollen Stage Against Low Temperaturementioning
confidence: 99%
“…In Japanese pears (P. pyrifolia Nakai), there are many studies on the influence of low temperatures on female organs (Oya, 2012;Sakuma et al, 2013;Sato, 1982;Sekozawa et al, 2003), but few on the effect upon pollen. Previously, it was reported that the tetrad to early microspore stage of pollen development was most sensitive to low temperature in Japanese pears (Hirata, 2000), but low-temperature sensitivity among cultivars and temperatures at which damage occurs remain unclear.…”
Section: Introductionmentioning
confidence: 99%